Vitamin D status and asthma, lung function, and hospitalization among British adults - Zhu, Yiqun; Jing, Danrong; Liang, Huaying; Li, Dianwu; Chang, Qinyu; Shen, Minxue; Pan, Pinhua; Liu, Hong; Zhang, Yan (Frontiers in Nutrition, 2022)
Background Vitamin D has been known to be associated with asthma. However, the association between vitamin D status and asthma, lung function as well as hospitalization among adults remains unclear. Objective To investigate the role of serum vitamin D in asthma prevalence, lung function, and asthma control in adults. Methods Multivariable logistic regression was applied to assess the relationship between serum vitamin D and asthma prevalence, lung function (FEV1, FVC, and FEV1/FVC), current wheeze, and asthma-linked hospitalizations in a cross-sectional study of 435,040 adults aged 37–73 years old from the UK Biobank. Results Compared to vitamin D deficiency, the odds of asthma were decreased by 6.4% [adjusted odds ratio (aOR) = 0.936; 95% CI: 0.911–0.962; p < 0.001] and 9.8% (aOR = 0. 0.902; 95% CI: 0.877–0. 0.927; p < 0.001) in individuals with insufficient and optimal vitamin D concentration, respectively, in the fully adjusted model. In total asthmatic patients, serum vitamin D was obviously and positively related with FEV1 (β = 1.328 ml, 95% CI = 0.575–2.080), FVC (β = 2.018 ml, 95% CI = 1.127–2.908), and FEV1/FVC (β = 0.006%, 95% CI = 0.002–0.010). Asthmatic patients whose vitamin D level was in the deficient category had 9.3–19.9% higher odds of current wheeze than insufficient categories (aOR = 0.907; 95% CI: 0.861–0.957; p < 0.001) and optimal categories (aOR = 0.801; 95% CI: 0.759–0.845; p < 0.001), but the relationship between vitamin D and asthma hospitalization was not significant. Conclusion Vitamin D deficiency was related to higher odds of asthma and current wheeze, and lower lung function in a large sample size study of British adults. Our results indicate a potential positive impact of serum vitamin D on asthma occurrence and disease control in adults.